'Changing Lives': Using technology to promote desistance. (September 2017) - McGreevy, Gail
In October 2016 the Probation Board for Northern Ireland launched an app called 'Changing Lives', designed to assist offenders to desist from crime. 'Changing Lives' is the first app developed specifically to help offenders in Northern Ireland to desist from crime and become rehabilitated. Available on both Android and iOS, it enables offenders who have problems with their mental health or addictions to identify their problems and find support. It offers advice on how to overcome problems with addictions and mental health and signposts people to appropriate services. People who believe they are at risk can also directly ring the Samaritans or Lifeline from the app. The app features a journal, so that those on probation can keep track of any issues in their lives and share their progress or any challenges they face with their probation officer. A contacts section of the app enables people to ring directly through to probation staff as well as out-of-hours GP services and others. The app is due to be evaluated in October 2017.